Corn stover harvest reduces soil CO2 fluxes but increases overall C losses. Issue 11 (4th September 2020) - O'Brien, Peter L.; Sauer, Thomas J.; Archontoulis, Sotirios; Karlen, Douglas L.; Laird, David
Abstract: Harvesting corn ( Zea mays L.) stover for use as bioenergy feedstock may provide short‐term economic benefits and perhaps improve grain yield in continuous corn systems, but excessive stover removal may lead to long‐term depletion of soil C stocks. To better quantify the impacts of stover harvest on the soil C balance, we investigated CO2 fluxes under three harvest treatments (none, moderate, and high) in three continuous corn systems: (a) no tillage and no biochar applications, (b) chisel plowing with biochar amendments, and (c) chisel plowing without biochar amendments were quantified. We sampled static chambers 14, 13, and 15 times in 2010, 2011, and 2012, respectively, and the measurements were used to calibrate the Agricultural Production Systems sIMulator model. Although CO2 ‐C emissions did not differ among the three systems, both moderate (approximately 30%) and high (approximately 60%) stover removal rates reduced simulated CO2 ‐C emissions by nearly 10% and more than 22%, respectively. Despite these reductions in CO2 flux, the sum of CO2 ‐C and stover C exceeded CO2 ‐C losses in those plots without stover removal. This finding suggested soil C depletion was occurring for the soil and crop management practices used, even though depletion was not evident after 3 years. Application of biochar increased soil C levels, suggesting it may be able to offset some C losses. We conclude that for sustainable, highly productive agroecosystems that include stover harvest, all agronomic practices must be optimized to minimize C losses and maintain soil quality. Abstract : We quantified CO2 ‐C fluxes under three rates of corn stover removal, none, moderate, and high, in conventional tillage, no‐tillage, and biochar‐amended systems from 2010 to 2012. We found that stover removal decreased CO2 ‐C emissions across all systems; however, the amount of C removed in the corn stover still exceeded the reduction in CO2 ‐C emissions. Since stover removal did not show a consistent increase in biomass production, the findings suggest that repeated stover removal has the potential to deplete soil C stocks.